Epithelial mesenchymal transition and lung cancer - Xiao, Dakai (Pioneer Bioscience Publishing Company, 2010)
Despite the therapeutic advances, lung cancer remains the leading cause of cancer-related death in the United States and worldwide. Metastasis and recurrence are considered to be responsible for the failure of treatment. Recent studies indicate Epithelial mesenchymal transition, an evolutionarily conserved process, plays an important role in the embryonic development and cancer progression and is involved in the metastasis, drug resistance and correlated with progression of many tumors. Of importance, EMT is also involved in the acquisition of stemness phenotype of tumor cells. Although a growing body of evidence supports the role of EMT in the progression of many cancers, and a number of signal pathways, transcriptional factors and microRNAs involved in EMT process have been identified. However, the role of EMT in lung cancer is elusive. In this review, we present the recent findings in EMT including the molecular mechanisms of EMT, and the involvement of EMT in cancer progression, cancer stem cells and drug resistance, especially focusing on the correlation of EMT and lung cancer.